Beliefs über Beweise(n) im Mathematikunterricht – eine empirische Studie unter Lehramtsstudierenden (mathematica didactica, 2023)
Proofs play a central role in mathematics and are the characteristic tool for pursuing it. Thus, to convey an authentic view on mathematics in school, it is necessary facing proofs in mathematics classrooms. Nevertheless, they have largely disappeared from school curricula in recent years, which at the same time contributes to widening the gap between school and university mathematics and – among other reasons – can lead to difficulties for students. The latter is reflected, among other things, in high dropout rates in mathematics and science degree programs. Therefore, permanent integrating proofs into mathematics classrooms and reestablishing their reputation in school would be welcome. However, it would facilitate altering classroom practices if desired redesigning of mathematics in school fits with existing beliefs of mathematics teachers related to proofs. For getting a picture of pre-service teachers´ relevant experiences and existing beliefs, a questionnaire has been carried out. The data let suspect fragmentary and needy experiences with proofs in school on the one hand, but also promising overall picture of related beliefs on the other hand, which still should be slightly completed and modified to achieve the set aim to embedding of proofs in mathematics classrooms.